Failure of Therapeutic Anticoagulation in COVID-19 Patients With Acute Ischemic Stroke. A Retrospective Multicenter Study - Janes, Francesco; Gigli, Gian Luigi; Kuris, Fedra; Morassi, Mauro; Costa, Paolo; Nesi, Lorenzo; Giacomello, Roberta; Mazzacane, Federico; Leuci, Eleonora; Cavallini, Anna; Valente, Mariarosaria (Frontiers in Neurology, 2022)
Background. Acute ischemic stroke is a possible complication of Covid-19 infection. Although peculiar clinical features and underling specific mechanisms of thrombogenesis have been so far suggested, there is no consensus on the appropriate vascular preventive drug regimen in Covid19 patients. Aim and Methods. From a larger clinical series of consecutive acute ischemic strokes related to Covid-19, admitted to three cerebrovascular units in Northern Italy, herein we describe the clinical features of a subgroup of patients in whom stroke occurred despite therapeutic anticoagulation. Results. Seventeen/80 acute ischemic strokes related to Covid-19 (21,2%) occurred in anticoagulated patients. Their National Institute of Health Stroke Scale (NIHSS) at admission was 12,0 (SD = 7,4) and 58,8% of them had evidence of a large vessel occlusion. The case fatality rate was as high as 64,7%. Discussion and Conclusions. The occurrence of an anticoagulation failure seems to be increased in the setting of Covid-19 infection, with worse clinical outcome if compared to non-Covid-19 related ischemic strokes. We discuss diagnostic and therapeutic implications of such evidence, suggesting that some arterial thrombotic complications might be either resistant to or independent of anticoagulation effect.